2012
DOI: 10.1590/s0102-67202012000200003
|View full text |Cite
|
Sign up to set email alerts
|

Incidência e fatores predisponentes da migração da fundoplicatura pela técnica de Nissen-Rossetti no tratamento da doença do refluxo Gastroesofágico

Abstract: The incidence of the fundoplication migration was 18.8%. The gender (female) and higher age influence the probability of migration. The degree of esophagitis, size of hernia and enlargement of the cardia were not risk factors for intrathoracic migration of the fundoplication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Other studies have noted similar findings correlating BMI to failure rates [ 8 ]. Female and elderly patients have also been shown in 1 study to have a higher incidence of FO migration; however, sex and age have not correlated with failure rates in other investigations [ 9 ]. Interestingly, it has even been suggested that frequent belching and gagging may lead to higher rates of FO failure [ 10 ].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Other studies have noted similar findings correlating BMI to failure rates [ 8 ]. Female and elderly patients have also been shown in 1 study to have a higher incidence of FO migration; however, sex and age have not correlated with failure rates in other investigations [ 9 ]. Interestingly, it has even been suggested that frequent belching and gagging may lead to higher rates of FO failure [ 10 ].…”
Section: Introductionmentioning
confidence: 83%
“…It is important to note that the prior literature has also been inconsistent regarding the correlation between age and failure rates. One study demonstrated that older patients had a greater chance of FO migration; however, this has not been successfully replicated [ 9 ]. Given the variation in our findings and the current literature, further investigation still needs to be carried out before a true correlation between age and surgical failure rates can be established.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the most common symptoms / signs in the recent postoperative period are chest pain, dysphagia, and vomiting. Often such symptoms / signs are acute and there is strong association with increased intraabdominal pressure, which increases the risk of valve migration 6 . The investigation of the condition should be done through the esophagogram, visualizing the gastric fundus above the diaphragmatic crura, with narrowing of contrast passage 7 .…”
Section: To the Editorsmentioning
confidence: 99%